Effects of metformin on blood and urine pro-inflammatory mediators in patients with type 2 diabetes. Issue 1 (December 2016) - Chen, Wei; Liu, Xiaojie; Ye, Shandong
Abstract Background Metformin has been used for the treatment of type 2 diabetes by suppressing hepatic gluconeogenesis. It has been shown that the subclinical inflammatory responses play important roles in the pathogenesis of type 2 diabetes. In the present study, we determined the effects of metformin on the levels of pro-inflammatory cytokines (i.e., IL-6, TNF-α, and MCP-1) and anti-inflammatory mediator IL-10 in blood and urine of patients with type 2 diabetes. There were 210 patients with type 2 diabetes, which were randomized into metformin (n = 112) and non-metformin (gliclazide, acarbose, and repaglinide, n = 98) groups. The levels of cytokines were measured by the ELISA. Results We found that metformin reduced the levels of IL-6 in blood and MCP-1 in urine, but increased IL-10 levels in blood of patients with type 2 diabetes. There were no significant differences of TNF-α between metformin and non-metformin groups. Furthermore, compared to individual drug treatment, metformin significantly reduced the levels of serum IL-6 and TNF-α, as well as urine MCP-1. When the patients were stratified based on the durations and doses of metformin, we found that there was only change (i.e., increase) in serum IL-10 levels in patients with metformin for more than 1 year compared to treatment for less than 1 year. Metformin (1.5 g) treatment reduced the urinary levels of MCP-1 as compared with dose of 1.0 g in patients with type 2 diabetes. Conclusion Metformin reduces inflammatory responses without influence on renal function in type 2 diabetic patients.